Prospects for reforming criminal procedure (Academic Journal of Internal Affairs, 2018)
The author provides an overview of the most important, and most challenging aspects of the new Hungarian Criminal Procedural Code, the intention to speed up the process by making a deal with the offender. The article lists some of the possible benefits and risks of the chosen solutions.
Keywords: criminal procedure; prospects; risks